2000
DOI: 10.2134/agronj2000.924621x
|View full text |Cite
|
Sign up to set email alerts
|

A Sampling Method for Measurement of Large Root Systems with Scanner‐Based Image Analysis

Abstract: Measurement of relatively small (<100 m total length, <6 g fresh wt.) root systems has been simplified by image analysis, but measuring larger root systems remains time‐consuming and inaccurate. Reliability of root estimation can be improved through identification of effective sampling methods. We devised a system for the collection of homogeneous root subsamples by air‐stirring in water. We optimized the subsampling technique and used a scanner‐based image analysis system to measure total root length, mean ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 35 publications
(40 reference statements)
1
59
0
5
Order By: Relevance
“…Thereby, scanning an entire root system of a single 45-day-old bean plant requires 4 hours and 53 minutes (±58 minutes), being a very laborious task that hampers its execution for a large number of plants. The amount of root placed on the sheet affects the accuracy of the estimates, since too many roots increase overlapping and crossing over (Costa et al, 2000), and depending on the size of sample, spreading roots can be very time-consuming (Richner et al, 2000). Bean root samples in the mounted sheets had mean dry mass of 60±11 mg and length of 7.4±1.1 m. Studying a digital line-intercept method, Farrell et al (1993) observed less variability on wheat (Triticum aestivum L.) root samples with total length varying from 2 to 4 m.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thereby, scanning an entire root system of a single 45-day-old bean plant requires 4 hours and 53 minutes (±58 minutes), being a very laborious task that hampers its execution for a large number of plants. The amount of root placed on the sheet affects the accuracy of the estimates, since too many roots increase overlapping and crossing over (Costa et al, 2000), and depending on the size of sample, spreading roots can be very time-consuming (Richner et al, 2000). Bean root samples in the mounted sheets had mean dry mass of 60±11 mg and length of 7.4±1.1 m. Studying a digital line-intercept method, Farrell et al (1993) observed less variability on wheat (Triticum aestivum L.) root samples with total length varying from 2 to 4 m.…”
Section: Resultsmentioning
confidence: 99%
“…It must be noticed that a single plant was grown per pot, and each root sample corresponded indeed to one mounted acetate sheet. Studies with maize plants indicated that samples with 10% (Costa et al, 2000) or 20% (Rossiello et al, 1995) of total root volume produced satisfactory estimation of root length. The results of the present work indicate root samples of almost 15% of total root mass for estimating root traits of common bean.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Root morphology determines the ability of the plant to acquire soil resources (Costa et al, 2000;Shi et al, 2015). R. pseudoacacia seedlings decreased TRL and TRSA, which suggested that the ability of ion and water uptake decreased (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%